2022
DOI: 10.3390/jcm11082227
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Cumulative Incidence of COVID-19 Cases on the Mental Health of the Spanish Out-of-Hospital Professionals

Abstract: This study aimed to analyze the psychological affectation of health professionals (HPs) of Spanish Emergency Medical Services (EMSs) according to the cumulative incidence (CI) of COVID-19 cases in the regions in which they worked. A cross-sectional descriptive study was designed, including all HPs working in any EMS of the Spanish geography between 1 February 2021 and 30 April 2021. Their level of stress, anxiety and depression (DASS-21) and the perception of self-efficacy (G-SES) were the study's main results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In the same year, Raúl Soto-Cámara et al surveyed professionals in the emergency medical system in Spain. They indicated that emergency medical technicians were more psychologically stressed than other professionals [3]. In an Iranian study, ethnic groups similar to those in Taiwan suggested that psychological stress was significantly associated with working hours per week and living away from family; sleep quality was not mentioned as a factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the same year, Raúl Soto-Cámara et al surveyed professionals in the emergency medical system in Spain. They indicated that emergency medical technicians were more psychologically stressed than other professionals [3]. In an Iranian study, ethnic groups similar to those in Taiwan suggested that psychological stress was significantly associated with working hours per week and living away from family; sleep quality was not mentioned as a factor.…”
Section: Discussionmentioning
confidence: 99%
“…In the same year, Raúl Soto-Cámara et al surveyed professionals in the emergency medical system in Spain. They indicated that emergency medical technicians were more psychologically stressed than other professionals [3]. In an Iranian…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 Long work hours, strict instructions and safety procedures, a constant need for focus and alertness, restricted social connection, and participation in tasks for which they may not be trained are all examples of exceptionally high job-related stressors. 4 , 5 These stressors have been linked to medical personnel’s emotional distress during the COVID-19 pandemic, which may have become a source of anxiety. 6 , 7 According to recent research, medical professionals may be experiencing the highest levels of anxiety 8 because they are often responsible for treating COVID-19 patients and are more psychologically stressed.…”
Section: Introductionmentioning
confidence: 99%